The Political performance of romantic intellectuals (writers, journalists, and academics) during the dictatorship of Colonel Mariano Ignacio Prado (1865-1868) - Pérez Garay, Carlos (2023)
This study is part of a larger investigation. The relationship that some intellectuals of Romantic generation had with the political power of Colonel Mariano Ignacio Prado, a military leader who governed Peru between 1865 and 1868, will be shown in this article. Compromise, loyalty, discrepancy, and opposition were the political attitudes most adopted by the members of the enlightened elite, which emerged in the mid-19th century. The following pages will describe these approaches.